(untitled) (Al-Qamar, 2020)
A judge is a pillar of our entire justice system. He is supposed to be a righteous, virtuous, pious, honest, and unbiased person who led a blameless life. Judges must endeavor for the utmost standards of integrity in both their professional and personal lives. He should be knowledgeable about the law (fiqh, Sharī’ah), probing, willing to undertake in-depth legal research, and able to write decisions that are clear, logical and cogent. In Islamic law, a Qazi is comparable to a magistrate or judge in contemporary Western judicial systems. As well as adjudicating disputes, the qazi performs extrajudicial functions, including mediation and managing public works.‍ Within customary justice systems, the Qāzis and religious leaders at large — imams, muftis and the like — occupy a special place. Given their social status, and their knowledge of the Qur’an, they are perceived as the key institution for the ‘preservation of Muslim law’. This study will explore the qualities that an ideal judge (Qāzī) should embody, and the required skills in decision making, conflict resolution and problem solving in the light of Islamic teachings. This study will also point-out the barriers to achieving and exercising those skills and identify number of ways of for judges to be manifested as good judge.